2002
DOI: 10.1007/s00294-002-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of the pathogenic yeast Candida parapsilosis

Abstract: Candida parapsilosis is an important human pathogen, responsible for severe cases of systemic candidiasis and one of the leading causes of mortality in neonates. In this report, we describe the first system for genetic manipulation of C. parapsilosis. We isolated and subsequently determined DNA sequences of genes encoding galactokinase ( CpGAL1) and orotidine-5'-phosphate decarboxylase ( CpURA3) from a genomic DNA library of C. parapsilosis by functional complementation of corresponding mutations in Saccharomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
29
0
1
Order By: Relevance
“…Molecular genetic studies of C. parapsilosis have been hindered by the aneuploidy of the organism (22) and the lack of a characterized sexual cycle. A transformation system based on the complementation of a galactokinase-deficient mutant of C. parapsilosis by the homologous gene (GAL1) has been described, but it lacks efficiency and cannot be used to inactivate target genes in prototrophic WT strains (23). Our studies demonstrate that the SAT1 flipper cassette is an efficient tool to generate homozygous KO mutants in C. parapsilosis.…”
Section: Discussionmentioning
confidence: 89%
“…Molecular genetic studies of C. parapsilosis have been hindered by the aneuploidy of the organism (22) and the lack of a characterized sexual cycle. A transformation system based on the complementation of a galactokinase-deficient mutant of C. parapsilosis by the homologous gene (GAL1) has been described, but it lacks efficiency and cannot be used to inactivate target genes in prototrophic WT strains (23). Our studies demonstrate that the SAT1 flipper cassette is an efficient tool to generate homozygous KO mutants in C. parapsilosis.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, until 2007 an efficient method for targeted gene disruption to generate mutants for the identification of C. parapsilosis virulence factors did not exist. A transformation system based on the complementation of a galactokinase-deficient mutant of C. parapsilosis by the homologous gene (GAL1) was described in 2002, but it could not be used to target genes in prototrophic wild-type strains (191). We previously showed that the dominant selection marker MPA R can be used for C. parapsilosis transformation (94), and we created an improved system for efficient gene deletion based on the repeated use of the dominant nourseothricin (Nou) resistance marker (CaSAT1) and its subsequent deletion by site-specific recombination (97) as previously described for C. albicans (227).…”
Section: Molecular Manipulationsmentioning
confidence: 99%
“…Expression studies of CpLIP genes using other yeasts highly contributed to our knowledge on C. parapsilosis lipase secretion, but did not address their role in virulence. Although there were advances in C. parapsilosis genetic manipulation [12,54] , it was not until 2007 that an innovative method for targeted gene deletion became available, and LIP1 -LIP2 were one of the first genes to be deleted from the diploid genome of C. parapsilosis, using a dominant selection marker carrier flipper cassette [34]. The available null mutant strain (Cp ΔΔlip1-ΔΔlip2) provided us a novel tool for studying C. parapsilosis lipases and facilitated numerous subsequent virulence related investigations.…”
Section: Identification Of C Parapsilosis Secreted Lipasesmentioning
confidence: 99%